2022
DOI: 10.3389/fmolb.2022.915993
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Non-Coding RNAs in Primary Biliary Cholangitis

Abstract: Primary biliary cholangitis (PBC) is an autoimmune-mediated chronic cholestatic liver disease, fatigue, and skin itching are the most common clinical symptoms. Its main pathological feature is the progressive damage and destruction of bile duct epithelial cells. Non-coding RNA (NcRNA, mainly including microRNA, long non-coding RNA and circular RNA) plays a role in the pathological and biological processes of various diseases, especially autoimmune diseases. Many validated ncRNAs are expected to be biomarkers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…A study by Tan and colleagues observed that serum levels of miR-122-5p are elevated in PBC patients and suggested that a panel of three miRNAs (miR-122-5p, miR-141-3p, and miR-26b-5p) could be a more sensitive and specific marker than ALP and ANA to diagnose PBC. miRNA-122 regulates many cell functions, among others, lipid metabolism, cell differentiation, acetaminophen toxicity, liver fibrosis in innate immunity, and may play a role in the proliferation and apoptosis of intrahepatic bile duct cells [63]. The expression of this miRNA has also recently been investigated in HCC patients, and surprisingly, its decreased expression was found to be associated with metastasis in HCV-negative HCC [64].…”
Section: Shared Molecular Alterations In Pbc and Hccmentioning
confidence: 99%
“…A study by Tan and colleagues observed that serum levels of miR-122-5p are elevated in PBC patients and suggested that a panel of three miRNAs (miR-122-5p, miR-141-3p, and miR-26b-5p) could be a more sensitive and specific marker than ALP and ANA to diagnose PBC. miRNA-122 regulates many cell functions, among others, lipid metabolism, cell differentiation, acetaminophen toxicity, liver fibrosis in innate immunity, and may play a role in the proliferation and apoptosis of intrahepatic bile duct cells [63]. The expression of this miRNA has also recently been investigated in HCC patients, and surprisingly, its decreased expression was found to be associated with metastasis in HCV-negative HCC [64].…”
Section: Shared Molecular Alterations In Pbc and Hccmentioning
confidence: 99%
“…Based on several studies, various miRNAs are dysregulated in PBC, and these dysregulation leads to the development and progression of PBC. 18,19…”
Section: Epigenetic Modificationsmentioning
confidence: 99%